An Analysis of Students’ Writing Anxiety and Strategies Used in Writing English Journal Article - Tiara Afdalia; Akhmad Ali Mirza; Hesty Widiastuty (JELITA, 2023)
Writing is one of the productive skills that English learners must possess in a foreign language. Writing anxiety in compiling and arranging words can occur to students, especially writing journal articles. This study examined (i) the most dominant types of students’ writing anxiety, and (ii) the strategies used to overcome their anxiety in writing English journal articles. The participants in this study were 40 students of the English Education study program at IAIN Palangka Raya who had written English journal articles. This study used mixed-methods sequential explanatory approach. The findings of this study indicated cognitive anxiety was the most dominant type of writing anxiety, followed by somatic anxiety, and the last type of writing anxiety was avoidance behavior in writing English journal articles. Furthermore, the strategies used to overcome anxiety in writing were (i) making a self-suggestion to be calm and think positively, (ii) looking for other articles with good credibility as references, and (iii) building simple English writing habits in daily activity. According to this research, the strategy used by students in the cognitive aspect by discussing with the lecturer or some experts about the tips for writing a journal article may be a novel to overcome the anxiety, especially in writing English journal articles.